54th AIAA Aerospace Sciences Meeting 2016
DOI: 10.2514/6.2016-0319
|View full text |Cite
|
Sign up to set email alerts
|

Open-Loop and Closed-Loop Trailing-Edge Separation Control on a Natural Laminar Flow Airfoil

Abstract: Active Unsteady Flow Control experiments were performed on a Natural Laminar Flow, NLF 0414 airfoil at Rec = 1.0 × 10 6 in a 3-ft × 4-ft low-speed, low-turbulence wind tunnel. The NLF 0414 was designed with a region of favorable pressure gradient extending almost 70% of the chord on the upper surface of the airfoil. Aggressive pressure recovery in the aft 30% of the chord near the trailing edge results in the separation of the flow from the airfoil surface at the off-design conditions. The goal of this study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Investigations of CLC systems controlling the flow separation through the fluidic devices can concern a wide spectrum of lifting surfaces such as: airfoils (Gupta and Ansell, 2016; Pinier et al , 2007), compressor blades (Bright et al , 2005) and high-lift systems (Chabert et al , 2013, 2014). Within this area, the studies of Seifert et al (1996), Seifert and Pack (1999) and the Darabi and Wygnanski (2004) showed that periodic blowing or suction is more efficient than steady blowing or steady suction.…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of CLC systems controlling the flow separation through the fluidic devices can concern a wide spectrum of lifting surfaces such as: airfoils (Gupta and Ansell, 2016; Pinier et al , 2007), compressor blades (Bright et al , 2005) and high-lift systems (Chabert et al , 2013, 2014). Within this area, the studies of Seifert et al (1996), Seifert and Pack (1999) and the Darabi and Wygnanski (2004) showed that periodic blowing or suction is more efficient than steady blowing or steady suction.…”
Section: Introductionmentioning
confidence: 99%